Hubungan Antara Dukungan Sosial Keluarga Dengan Resiliensi Pada Pasien Gagal Ginjal Yang Menjalani Terapi Hemodialisia - TITISARI, ARUMINGTYAS; , Dr. Wiwien Dinar Pratisti, M.Si, P.si (2017)
The purpose of this research was: 1) To determine the relationship between social support of families with resilience in patients with renal failure undergoing hemodialysis therapy. 2) To determine the level of family support and the level of resilience in renal failure patients undergoing hemodialysis therapy. 3) To determine the effectiveness of the contribution of social support to the family of resilience in renal failure patients undergoing hemodialysis therapy. The hypothesis is a positive relationship between social support of families with resilience in patients with renal failure undergoing hemodialysis therapy. Subjects in this study were 56 patients with renal failure undergoing hemodialysis therapy. The measuring instruments used were used in this study are: a) Scale resilience and b) social support scale family. Data analysis techniques used in this study is the product moment correlation. I get the results of the analysis are consistent with the hypothesis put forward is, there is a significant positive relationship between social support of families with resilience in patients with renal failure undergoing hemodialysis therapy. The higher the social support of the family, the higher the resilience of renal failure patients undergoing hemodialysis therapy, conversely the lower the social support of the family, the lower the resilience in renal failure patients undergoing hemodialysis therapy. This is indicated by the value (rxy) of 0.832; significance (p) 0,000; (P <0.01). Donations effectiveness (SE) family support against the resilience of renal failure patients undergoing hemodialysis therapy amounted to 69,22%. It is still 30,78% are other variables that can affect the resilience of renal failure patients undergoing hemodialysis therapy outside the family social support variables. Keywords: Social Support Family, Resilience, Kidney Failure Patients Undergoing Hemodialysis Therapy